(untitled) (Phenomenology, Humanities and Sciences, 2020)
Viktor Frankl’s Logotherapy is based on Max Scheler’s theory of values and anthropology. Frankl builds his psychological thinking based on critical concepts of Schelerian thinking such as (i) value and goods, (ii) will and feelings, (iii) the hierarchy of values, and (iv) the idea of person. It is with them that he develops his original theses of (i) the spiritual motivation of human action, (ii) the search for meaning and (iii) the spiritual unconscious. In doing so, he offered not only a psychotherapy of values, but also a new theory of positive human motivation, not conceived as a result of deficiency or need, but as a result of the free spirit toward objective values. The human search for meaning in life can only be successful by living and realizing superior values, in the hierarchical sense proposed by Scheler.